English Learning using Blended Learning and Missing Pieces Activities Methods - Mimin Aminah (Jurnal Scientia, 2021)
At this time the development of information technology is growing very rapidly. This development can certainly be used in various aspects of human life, and one of them is in the education sector. Blended Learning is a learning method that is produced by utilizing the development of technology and information. The influence is clearly visible, one of which is the learning method. The learning method that used to be done only face-to-face in the classroom and made educators as an information center (conventional) gradually began to change towards learning which is also online based on the internet as an information center. This study uses a descriptive method and a qualitative approach to produce a conclusion that, briefly, the use of Blended learning in the development of English lessons is a new method that combines the e-Learning system with conventional or face-to-face methods. Finally, the role of technology can provide a new learning method that takes place actively, openly and provides a different atmosphere when students are in class, through the Missing Pieces Activities technique and line application, English language learning is applied by providing various kinds of learning activities which include: , listening activities (with Missing Words), speaking activities (with Missing Small Thing), and reading activities (with Missing Sentences) on the other hand the use of line applications for the English learning process is carried out by uploading several practice questions, including major in the discussion of reading and speaking